Modulation of Buckling Dynamics in Nanoparticle Laden Droplets Using External Heating - Pathak, Binita (Langmuir : the ACS journal of surfaces and colloids, 2016)
Dynamics of contact free (levitated) drying of nanofluid droplets is ubiquitous in many application domains ranging from spray drying to pharmaceutics. Controlling the final morphology (macro to micro scales) of the dried out sample poses some serious challenges. Evaporation of solvent and agglomeration of particles leads to porous shell formation in acoustically levitated nanosilica droplets. The capillary pressure due to evaporation across the menisci at the nanoscale pores causes buckling of the shell which leads to ring and bowl shaped final structures. Acoustics plays a crucial role in flattening of droplets which is a prerequisite for initiation of buckling in the shell. Introduction of mixed nanocolloids (sodium dodecyl sulfate + nanosilica) reduces evaporation rate, disrupts formation of porous shell, and enhances mechanical strength of the shell, all of which restricts the process of buckling. Although buckling is completely arrested in such surfactant added droplets, controlled external heating using laser enhances evaporation through the pores in the shell due to thermally induced structural changes and rearrangement of SDS aggregates which reinitializes buckling in such droplets. Furthermore, inclusion of anilinium hydrochloride into the nanoparticle laden droplets produces ions which adsorb and modify the morphology of sodium dodecyl sulfate crystals and reinitializes buckling in the shell (irrespective of external heating conditions). The kinetics of buckling is determined by the combined effect of morphology of the colloidal particles, particle/aggregate diffusion rate within the droplet, and the rate of evaporation of water. The buckling dynamics leads to cavity formation which grows subsequently to yield final structures with drastically different morphological features. The cavity growth is controlled by evaporation through the nanoscale pores and exhibits a universal trend irrespective of heating rate and nanoparticle type